Committed to Print : Social and Political Themes in Recent American Printed Art - Wye, Deborah (New York : The museum of Modern Art, 1988)
Acconci, Vito ; Allyn, Jerri ; Alonso, Luis ; Amos, Emma ; Andrews, Benny ; Applebroog, Ida ; Arai, Tomie ; Arneson, Robert ; Avery, Eric ; Azaceta, Luis Cruz ; Balassanian, Sonia ; Baranik, Rudolf ; Bearden, Romare ; Becker, Nan ; Begay, Rudy ; Bender, Leslie ; Borofsky, Jonathan ; Bourgeois, Louise ; Browne, Vivian ; Burden, Chris ; Camnitzer, Luis ; Carvalho, Josely ; Catlett, Elizabeth ; Chicago, Judy ; Cockcroft, Eva ; Coe, Sue ; Corris, Michael ; Cortez, Carlos ; van Dalen, Anton ; Dickson, Jane ; Dine, Jim ; Dong, James ; Edelson, Mary Beth ; Edwards, Melvin ; Elliot, Marguerite ; Fekner, John ; Frank, Mary ; Frasconi, Antonio ; Garcia, Rupert ; Gilbert, Sharon ; Gleeson, Day ; Glier, Mike ; Golub, Leon ; Gourfain, Peter ; Granet, Ilona ; Group Material ; Guerrero-Cruz, Dolores ; Guerrilla Art Action Group (GAAG) ; Gutiérrez, Marina ; Haacke, Hans ; Hammons, David ; Haring, Keith ; Heap-of-Birds, Edgar ; Heresies Collective ; Holzer, Jenny ; Howland, Rebecca ; Huang, Arlan ; Indiana, Robert ; Irizarry, Carlos ; Jaar, Alfredo ; Jimenez, Luis ; Johns, Jasper ; Kearns, Jerry ; Kienholz, Edward ; Klayman, Leon ; Koenig, Janet ; Kramer, Margia ; Kruger, Barbara ; Lacy, Suzanne ; LaMarr, Jean ; Lawrence, Jacob ; Lebrón, Michael ; Lee, Colin ; Levine, Jack ; Levine, Les ; Longo, Robert ; Marcus, Paul ; Marisol ; McAdams, Dona Ann ; Mock, Richard ; Moore, Sabra ; Morris, Robert ; Nauman, Bruce ; Nechvatal, Joseph ; Oldenburg, Claes ; Paschke, Ed ; Piper, Adrian ; Pyzow, Susan ; Rauschenberg, Robert ; Ringgold, Faith ; Rivers, Larry ; Rodriguez, Elizabeth ; Rollins, Tim & K.O.S. ; Romero, Rachel ; Rosenquist, James ; Rosler, Martha ; Rothenberg, Erika ; Rupp, Christy ; Sances, Jos ; Sanchez, Juan ; Saul, Peter ; Schapiro, Miriam ; Shahn, Ben ; etc.
Committed to Print : Social and Political Themes in Recent American Printed Art, The Museum of Modern Art, New York, January 31 to April 19, 1988
boek